Impact of right-sided breast cancer adjuvant radiotherapy on the liver - Hanedan Uslu Gonca; Taşçı Filiz (Radiology and Oncology)
In patients with right-sided breast cancer the liver can be partially irradiated during adjuvant radiotherapy (RT). We aimed to determine breast cancer RT effects on liver using with magnetic resonance elastography (MRE) and biological results.